IOT Power System MQTT Protocol at Micro-Scale Shrimp Farming in Urban Areas - Agung Kridoyono; Mochamad Sidqon; Anton Breva Yunanda; Ameloddin Amimus (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2022)
In the post-pandemic era, Food security is activity that recommended by the government to save food crisis especially to increase food activity in urban areas. Like a shrimps, is the most favorite fish for food at urban area where in general this fish cultivation is carried out in the pond area. With the IOT MqTT protocol we propose the model of prototype system of shrimp cultivation at urban area where the place had topography characteristic like 5-9meter ground level, 31 °C temperature and 71%humidity. with the MQTT mobile telemetry we get the information about the changes condition like a temperature, PH, turbidity at the pond based android. Temperature for the heat level, PH for acidity and turbidity for clarity. Using wifi microcontroller AVR based to connect firebase cloud for storing data sensor that input data MUX microcontroller get from analog sensor. The power plant using solar power that implemented for power system at the peripheral. The result is the information condition of pond and alert if the value is out of set point value in the shrimp pond also the model of solar power system that implemented of shrimp farming.